Sustainability evaluation of different techniques for concrete mixing based on quality control - Reynosa-Morales, L. M.; Olguín-Coca, F. J.; Guillén-Trujillo, H. A.; Alonso-Farrera, F. A.; Castro-Borges, P.; López-González, A.; Ramos-Torres, G. (Revista ALCONPAT, 2017)
In this study emergy analysis, an environmental valuation method was applied to concrete mixing with the purpose of evaluating its dependence on non-renewable natural resources. Three concrete mixing techniques, industrialized, semi-industrialized and manual, were evaluated based on quality control. The quantity of environmental resources used in production was measured in terms of equivalent solar energy. The resulting transformities were compared to show that emergy analysis is sensible to local context and the limits of the reference system. The results obtained show that concrete mixing is highly dependent on external resources. Semi-industrialized concrete was found to be the most sustainable.